2020
DOI: 10.34172/npj.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Potential of renin-angiotensin system inhibition to improve metabolic bone disorders

Abstract: Metabolic bone disorder is an abnormality of bones indicated by reduced bone mass and high risk of fractures. Several lines of evidence have demonstrated that the local bone tissue renin-angiotensin system (RAS) is directly involved in bone metabolism and influences the bone health. This review aimed to assess the role of RAS in bone metabolism and comparative effectiveness of angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) in reducing the bone fractures. In summary, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…AT1R has been identified in osteoclast precursors and mature osteoclasts, indicating that the RAS may directly impact bone metabolism ( 46 ). In addition, several studies have shown that blocking AT1R with drugs can have beneficial effects on bone metabolism, potentially by reducing osteoclastogenesis and bone resorption ( 47 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…AT1R has been identified in osteoclast precursors and mature osteoclasts, indicating that the RAS may directly impact bone metabolism ( 46 ). In addition, several studies have shown that blocking AT1R with drugs can have beneficial effects on bone metabolism, potentially by reducing osteoclastogenesis and bone resorption ( 47 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…LDLmediated cholesterol administration improves osteoclast survival, and hence their lifespan, considerably [108,109]. Therefore, Ang II modifies Cbfa1 expression, consequently reducing the number of osteoblasts and resulting in poor bone formation by stimulating the cAMP signaling pathway and regulating other downstream targets such as LDLs [110,111]. Ang II triggers prostaglandins, which stimulate cAMP signaling, leading to upregulated expression of LDL receptors [112].…”
Section: Ang II Increases Cyclic Adenosine Monophosphate (Camp)mentioning
confidence: 99%
“…(4) It has been suggested that the risk of hip fractures is reduced with the use of ACE inhibitors and ARBs. (5) A study demonstrated a positive effect on the healing of fractures of enalapril, as an ACE inhibitor, in contrast to losartan, as an ARB, which did not show a positive effect. (6) The use of enalapril leads to increased blood flow and improved microcirculation in the fracture zone, which provides an appropriate microenvironment for osteoblast activity to produce bone matrix.…”
Section: Introductionmentioning
confidence: 99%